Nonmagnetic single-molecule spin-filter based on quantum interference - Atindra Nath Pal (Nature Portfolio, 2019)
Quantum interference can be used to control electronic transport with high sensitivity at the nanoscale. Pal et al. show that without the need for magnetic materials, quantum interference can also filter spin transport approaching the limit of ideal spin-polarized ballistic transport in molecular junctions.